Evaluating Physical Outcomes in Acute Respiratory Distress Syndrome Survivors: Validity, Responsiveness, and Minimal Important Difference of 4-Meter Gait Speed Test*. Issue 5 (May 2016) - Chan, Kitty S.; Aronson Friedman, Lisa; Dinglas, Victor D.; Hough, Catherine L.; Morris, Peter E.; Mendez-Tellez, Pedro A.; Jackson, James C.; Ely, E. Wesley; Hopkins, Ramona O.; Needham, Dale M.
Abstract : Objective: To examine the reliability, validity, responsiveness, and minimal important difference of the 4-m gait speed test in acute respiratory distress syndrome survivors. Design: Secondary analyses of data from two longitudinal follow-up studies of acute respiratory distress syndrome survivors. Test-retest and inter-rater reliability, construct validity (convergent, discriminant, and known group), predictive validity, and responsiveness were examined. The minimal important difference was estimated using anchor- and distribution-based approaches. Setting: A national multicenter prospective study (ARDSNet Long-Term Outcome Study) and a multisite prospective study in Baltimore, MD (Improving Care of Acute Lung Injury Patients). Patients: Acute respiratory distress syndrome survivors with 4-m gait speed assessment up to 60 months after acute respiratory distress syndrome (ARDSNet Long-Term Outcome Study, n = 184; Improving Care of Acute Lung Injury Patients, n = 122). Interventions: Not applicable. Measurements and Main Results: Four-meter gait speed was assessed at 6- and 12-month follow-up (ARDSNet Long-Term Outcome Study) and 36-, 48-, and 60-month follow-up (Improving Care of Acute Lung Injury Patients). Excellent test-retest (intraclass correlation, 0.89–0.99 across studies and follow-up) and inter-rater (intraclass correlation, 0.97) reliability were found. Convergent validity was supported by moderate-to-strong correlations (69% of 32 > 0.40) with other physical function measures. Discriminant validity was supported by weak correlations (86% of 28 < 0.30) with mental health measures. Survivors with impaired versus nonimpaired measures of muscle strength and pulmonary function had significantly slower 4-m gait speed (all but one p < 0.05). Furthermore, 4-m gait speed significantly predicted future hospitalization and health-related quality of life. Gait speed changes were consistent with reported changes in function, supporting responsiveness. The estimated 4-m gait speed minimal important difference was 0.03–0.06 m/s. Conclusions: The 4-m gait speed is a reliable, valid, and responsive measure of physical function in acute respiratory distress syndrome survivors. The estimated minimal important difference will facilitate sample size calculations for clinical studies evaluating the 4-m gait speed test in acute respiratory distress syndrome survivors. Abstract : Supplemental Digital Content is available in the text.